Effects of repetitive transcranial magnetic stimulation (rtms) treatment in comorbid nicotine addiction with major depressive disorder and obsessive-compulsive disorder - Yaşar, Asena Uzdu; Cinemre, Buket; Erdoğan, Ali (Journal of Dependence, 2022)
Objective: Nicotine addiction is a common health problem in psychiatric disorders. The aim of this study was to analyze the effects of rTMS on comorbid nicotine addiction in patients receiving recurrent Transcranial Magnetic Stimulation (rTMS) therapy for major depressive disorder (MDD) and obsessive-compulsive disorder (OCD). Method: Data of 32 patients (23 MDD, 9 OCD) were evaluated retrospectively. We compared the Hamilton Depression Rating Scale (HAM-D), Beck Anxiety Inventory (BAS), Yale-Brown Obsession Compulsion Scale (Y-BOCS), and Fagerström Test for Nicotine Dependence (FTND) scores at three time points (before treatment “0th week”, at the end of treatment “6th week”, and 12 weeks after this assessment “18th week”). Results: The patients’ mean age was 40.47±10.20, 13 (40.6%) were women. A significant reduction was found in HAM-D, BAS, FTND at weeks 6 (p<0.001 for all) and 18 (p<0.001 for all) compared to baseline scores. A binary logistic regression showed that changes in depression and anxiety symptoms were not associated with the changes in FTND ratings at weeks 6 and 18 (p=0.158, p=0.251, respectively). Conclusion: In this study, it can be said that rTMS treatment reduces the severity of nicotine addiction accompanying MDD and OCD, independent of the recovery of the psychiatric disease. This study suggests that rTMS can be an effective treatment for nicotine addiction comorbid with psychiatric disorders. We recommend placebo-controlled randomized double-blind studies.